TEACHING AND LEARNING MATHEMATICS THROUGH WEB-BASED RESOURCE: AN INTERACTIVE APPROACH - Kartika, Hendra (MaPan : Jurnal Matematika dan Pembelajaran, 2018)
Abstract: The aim of this study is to investigate the effectiveness of teaching and learning process using web-based resource as an interactive approach in learning mathematics. Research method used in this study is content analysis. The web-based resource in this study is interactive mathematics website. Based on this resource, teaching and learning mathematics is divided into three steps, first, teaching and learning to give student’s understanding on mathematics concepts and notation; second, teaching and learning interactive applet; and Student’s independent practices. After teaching and learning, sixty-nine students were given a feedback about teaching and learning mathematics through web-based resource enrolled in linear algebra course. The 12 questionnaires by (Hsu, 2017) ware used as the instrument to collect data on participant’s usage of web-based resource. Data analysis was conducted descriptively. The results of this study showed that there are positive feedback on students’ satisfaction and learning interest when using a web-based resource. Also, the results showed web-based resource could help students’ learning mathematics independently. Students can repeat and relearn the material that has been delivered anywhere and anytime. Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui efektifitas proses pembelajaran menggunakan bahan berbasis web sebagai pendekatan interaktif dalam belajar matematika. Metode penelitian yang digunakan adalah analisis konten. Sumber berbasis web dalam penelitian ini adalah website matematika interaktif. Berdasarkan sumber pembelajaran ini, pembelajaran matematika dibagi kedalam tiga langkah, yaitu pertama, pembelajaran untuk memberikan pemahaman siswa terhadap konsep dan notasi matematika; kedua, pembelajaran interaktif dengan applet; dan ketiga, latihan mandiri siswa. Setelah pembelajaran, 69 siswa yang mengikuti perkuliahan aljabar linear memberikan respon tentang pembelajaran matematika melalui sumber berbasis web. Instrumen yang digunakan adalah 12 kuesioner yang dikembangkan (Hsu, 2017). Hasil memperlihatkan bahwa terdapat respons positif dalam kepuasan dan minat belajar siswa ketika menggunakan sumber berbasis web. Hasil juga memperlihatkan bahwa sumber berbasis web dapat membantu siswa belajar matematika secara mandiri. Siswa dapat mengulang dan mempelajari kembali materi yang telah disampaikan kapan saja dan dimana saja.